2015
DOI: 10.18632/oncoscience.157
|View full text |Cite
|
Sign up to set email alerts
|

Circadian disruption-induced microRNAome deregulation in rat mammary gland tissues

Abstract: Breast cancer is the most common malignancy affecting women worldwide, and evidence is mounting that circadian-disruption-induced breast cancer is a warranted concern. Although studies on the role of epigenetics have provided valuable insights, and although epigenetics has been increasingly recognized in the etiology of breast cancer, relatively few studies have investigated the epigenetic link between circadian disruption (CD) and breast cancer. Using a proven photoperiod-shifting paradigm, differing degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…Interleukin-4 (IL-4) was identified as a B cell-stimulating factor critical for class-switch [52] . Circadian disruption also would result in aberrant changes to miRNAs [53] . Micro RNA (miRNA) was found to be involved in the regulation of TFH cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin-4 (IL-4) was identified as a B cell-stimulating factor critical for class-switch [52] . Circadian disruption also would result in aberrant changes to miRNAs [53] . Micro RNA (miRNA) was found to be involved in the regulation of TFH cells.…”
Section: Discussionmentioning
confidence: 99%
“…Micro RNA (miRNA) was found to be involved in the regulation of TFH cells. Abnormal control TFH could induce autoimmune disease [53] .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are an important molecular mediator of cell genetic changes, and are directly or indirectly associated with the occurrence and development of a number (6)(7)(8)(9)(10). Previous studies have indicated that Tudor-SN has a close association with lipid metabolism, and that the expression of lipoprotein in liver cells can be affected through adjustment of lipid metabolism-associated genes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, miRNAs seem to be a potential way in which to investigate biological timing processes that might be critical for cancer cells [ 18 , 19 ]. A recent study provides direct evidence that circadian disruption induces changes in miRNA levels in the mammary tissue of rats, which may lead to malignant consequences [ 20 ].…”
Section: Introductionmentioning
confidence: 99%